PUNISHMENT FOR INDIVIDUALS COMMITTING SEXUAL CRIMES AGAINST CHILDREN: A COMPARATIVE ANALYSIS OF POSITIVE AND TRADITIONAL CRIMINAL LAW IN INDONESIA - Wahyuni, Fitri; Irawan, Aris; Ayu, Riana Kesuma (Kanun Jurnal Ilmu Hukum, 2024)
The current punishment for sexual crimes against children, limited to imprisonment, is deemed ineffective in deterring perpetrators. This article delves into this issue through the lens of positive and customary criminal law. Employing a doctrinal method and drawing from various legal sources, the article reveals that the existing punishment under the Indonesian Criminal Code and Child Protection Laws fails to significantly reduce the incidence of such crimes. As a potential solution, traditional law could serve as supplementary punishment, involving corporal punishment or fines payable to the state treasury. This suggests that customary law could complement judicial sanctions. However, the implementation of such additional measures warrants evaluation to address other environmental factors that may contribute to these crimes.